2013
DOI: 10.5152/ucd.2013.11
|View full text |Cite
|
Sign up to set email alerts
|

Atypical localisation of a gastrointestinal stromal tumour: a case report of pancreas gastrointestinal stromal tumour

Abstract: An atypically localized gastrointestinal stromal tumor: a case report of pancreas gastrointestinal stromal tumor Gastrointestinal stromal tumors (GISTs) are the most common mesenchymal tumors of the gastrointestinal tract. They can arise from any part of the tract as well as the omentum, mesentery or retroperitoneum. In this study, we present a case of a GIST originating from an extraordinary site, the pancreas. Evaluation of 30-year-old man with complaints of abdominal distension revealed a cystic, distal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…GISTs that originate from the soft tissues of the abdomen and retroperitoneum are called extragastrointestinal stromal tumors (EGISTs). EGISTs that arise from the pancreas are extremely rare, and only 15 cases have been previously reported (7)(8)(9). Here we report a case of a large pancreatic EGIST that invaded the duodenum.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…GISTs that originate from the soft tissues of the abdomen and retroperitoneum are called extragastrointestinal stromal tumors (EGISTs). EGISTs that arise from the pancreas are extremely rare, and only 15 cases have been previously reported (7)(8)(9). Here we report a case of a large pancreatic EGIST that invaded the duodenum.…”
Section: Introductionmentioning
confidence: 79%
“…a hematopoietic progenitor cell antigen, whereas 20%-30% are positive for SMA and 10% are positive for the S-100 protein. Approximately 40%-60% of GISTs occur in the stomach, whereas 30%-40% occur in the small intestine, 10% in other parts of the gastrointestinal tract, and 5% elsewhere in the abdominal cavity (3,5,(8)(9)(10)(11)(12)(13)(14). GISTs are infrequent neoplasms.…”
Section: Case Presentationmentioning
confidence: 99%
“…These tumors most commonly occur in the stomach, with a frequency of 60–70% of all GISTs, followed by 20–25% in the small intestine, 5% in the colon and rectum, and < 5% in the esophagus [ 4 ]. Rarely, GIST occurs in the liver, gallbladder, pancreas, and bladder, and is called extragastrointestinal stromal tumor (EGIST), which accounts for < 5% of all GISTs [ 5 , 6 ]. A previous report indicated that < 5% of EGIST cases occur in the pancreas [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that, EGISTs are extremely rare, represent 5%-10% of all GISTs [7], [8]. EGISTs are frequently located in the omentum, mesentery or retroperitoneum [9].…”
Section: Discussionmentioning
confidence: 99%